Progress in the development of influenza vaccines: Memorandum from a WHO Meeting (1987)
Although influenza remains an important disease causing high levels of morbidity in many countries, the impact of epidemics can be reduced by immunoprophylaxis with available inactivated or cold-adapted live attenuated influenza vaccines. In closed or semi-closed communities, maximum benefit from immunization is likely to be achieved when more than 75% of the population are immunized. Other strategies to reduce the impact of influenza include mass immunization of certain populations to protect them as well as to reduce illness in the overall community. Adequate studies have not yet been undertaken to confirm whether the desired reduction in community-wide illnesses results from such target mass immunization programmes. Well-controlled studies to assess further the efficacy of influenza vaccines in not only protecting the vaccinee but also reducing the impact of influenza epidemics in the community should be encouraged.